THE IMPORTANCE OF PUBLIC SPENDING IN BRAZIL’S ECONOMIC DEVELOPMENT (2000 TO 2023) - Pereira Melesko, Cristiani (Revista Gênero e Interdisciplinaridade, 2024)
Public expenditure can influence economic development by increasing public investment. This study seeks to analyze the importance of public investments in education, health, infrastructure and human capital in the process of economic development. The objective of the article is to address, from a theoretical perspective, the relevance of public spending in Brazilian economic development. The research showed that an efficient allocation of public spending in different strategic, innovative areas with potential disseminators can influence and influence the country’s economic development.